1986
DOI: 10.1002/clc.4960091004
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function and coagulation studies in patients with mitral valve prolapse

Abstract: Summary: Twenty-eight consecutive patients with mitral valve prolapse (MVP), seven of whom had previous cerebrovascular disorders (CVD), were studied for platelet function and coagulation tests. While platelet function tests were found to be normal with the exception of platelet aggregation rate (PAR), there was a significant rise of factors VIII vWF:Ag (Von Willebrand) and (FPA) fibrinopeptide A. Six cases had high levels of both these factors, suggesting the existence of a particular subset of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…28 Zuppiroli et al have shown that platelet function tests were found to be normal with the exception of platelet aggregation rate. 29 In their study, there was a significant rise in von Willebrand factor and fibrinopeptide A levels, suggesting the existence of a particular subset of patients with MVP with a higher risk for thromboembolic events. 29 We evaluated the platelet reactivity by measuring MPV.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…28 Zuppiroli et al have shown that platelet function tests were found to be normal with the exception of platelet aggregation rate. 29 In their study, there was a significant rise in von Willebrand factor and fibrinopeptide A levels, suggesting the existence of a particular subset of patients with MVP with a higher risk for thromboembolic events. 29 We evaluated the platelet reactivity by measuring MPV.…”
Section: Discussionmentioning
confidence: 97%
“…29 In their study, there was a significant rise in von Willebrand factor and fibrinopeptide A levels, suggesting the existence of a particular subset of patients with MVP with a higher risk for thromboembolic events. 29 We evaluated the platelet reactivity by measuring MPV. Our findings are in accordance with those of previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One explanation for a high platelet count may be platelet fragmentation resulting from shear stress due to mitral regurgitation [2]. In addition, increased platelet reactivity has been reported in some human patients with mitral valve prolapse [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated increased platelet activation in patients with mitral regurgitation [3,19,20]. However, some opinions defending vice versa are also available [5].…”
Section: Discussionmentioning
confidence: 99%